Characterization and Mechanism of Linearized-Microcystinase Involved in Bacterial Degradation of Microcystins - Wei, Jia; Huang, Feiyu; Feng, Hai; Massey, Isaac Yaw; Clara, Tezi; Long, Dingxin; Cao, Yi; Luo, Jiayou; Yang, Fei (Frontiers in Microbiology, 2021)
Microcystins (MCs) are extremely hazards to the ecological environment and public health. How to control and remove MCs is an unsolved problem all over the world. Some microbes and their enzymes are thought to be effective in degrading MCs. Microcystinase can linearize MC-LR via a specific locus. However, linearized MC-LR is also very toxic and need to be removed. How linearized MC-LR was metabolized by linearized-microcystinase, especially how linearized-microcystinase bind to linearized MC-LR has not been defined. A combination of in vitro experiments and computer simulation was applied to explore the characterization and molecular mechanisms for linearized MC-LR degraded by linearized-microcystinase. The purified linearized-microcystinase was obtained by recombinant E. coli overexpressing. The concentration of linearized MC-LR was detected by high-performance liquid chromatography (HPLC), and linearized MC-LR degradation products were analyzed by the mass spectrometer. Homology modeling was used to predict the structure of the linearized-microcystinase. Molecular docking techniques on the computer were used to simulate the binding sites of linearized-microcystinase and linearized MC-LR. The purified linearized-microcystinase was obtained successfully. The linearized-microcystinase degraded linearized MC-LR to tetrapeptide efficiently. The second structure of linearized-microcystinase consisted of many alpha-helices, beta strands, and colis. Linearized-microcystinase interacted the linearized MC-LR with hydrogen bond, hydrophobic interaction, electrostatic forces and the Van der Waals force. This study firstly reveals the characterization and specific enzymatic mechanism of linearized-microcystinase for catalyzing linearized MC-LR. These findings encourage the application of MC-degrading engineering bacteria and build a great technique for MC-LR biodegradation in the environment engineering.